2021
DOI: 10.3758/s13428-021-01577-7
|View full text |Cite
|
Sign up to set email alerts
|

Cockroaches are scarier than snakes and spiders: Validation of an affective standardized set of animal images (ASSAI)

Abstract: Research on emotional processes has been closely related to the use of emotional stimuli, promoting the development of different standardized sets of images. However, some kinds of images that would be relevant in clinical psychology research are not available, especially for small animal phobias. The aim of the present study is to validate a set of animal images that includes images of cockroaches, which are not present in the current sets of images. Two hundred and forty images depicting five types of animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 45 publications
2
17
0
Order By: Relevance
“…We found them scoring low in fear, intermediate in disgust, and very low in beauty, where they ranked as the least beautiful of all the arthropod groups. This was surprising to us, given that in the study of Grimaldos García et al 41 , cockroaches were perceived very negatively even in comparison to spiders and snakes. However, that study did not look at fear or disgust, but rather valence and arousal ratings of a series of photographs.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…We found them scoring low in fear, intermediate in disgust, and very low in beauty, where they ranked as the least beautiful of all the arthropod groups. This was surprising to us, given that in the study of Grimaldos García et al 41 , cockroaches were perceived very negatively even in comparison to spiders and snakes. However, that study did not look at fear or disgust, but rather valence and arousal ratings of a series of photographs.…”
Section: Discussionmentioning
confidence: 61%
“…In line with the focus of our study, about half of the used species were chelicerates—15 spiders, 10 scorpions, and 5 other arachnids. Two specific arthropod phobias have been described—the already mentioned arachnophobia and the phobia of cockroaches 40 , 41 . For this reason, we also included 10 species of cockroaches, and 10 species of other hemimetabolous insects (i.e., four phasmids, two locusts, two praying mantises, a true bug, and an earwig) as a control group.…”
Section: Introductionmentioning
confidence: 99%
“…Certain limitation is that we used self‐report surveys and questions rather than structured diagnostic interviews. Finally, one might argue that having only 10 pictures per category (snakes and spiders) for evaluation can provide only limited information (see also Grimaldos et al, 2021), so the number of picture stimuli should be increased in future research. Although here we have used the dimensions of valence, arousal and dominance to evaluate the visual stimuli, there is another approach corresponding more to the concept of discrete emotions that would rate the pictures according to fear and disgust.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, mushroom images were replaced by cockroaches (Lobue, 2010). A recent study found that cockroaches were rated as significantly more unpleasant than snakes and spiders, while all three were viewed as equally arousing (Grimaldos et al, 2021). Therefore, this study included three image categories that were all high in arousal, while also providing the opportunity to differentiate between image categories by threat (snakes and spiders > cockroaches) and negative valence (cockroaches > snakes and spiders).…”
Section: Discussionmentioning
confidence: 99%